(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
With the entrance into force of the Regulation (EU) 2015/2283 on novel foods, a centralised assessment and authorisation procedure has been introduced to make the overall process more efficient. In this framework, the European Commission is responsible for authorising novel foods but can ask the European Food Safety Authority (EFSA) to conduct a scientific risk assessment to establish their safety. This chapter provides a brief overview of the European framework on novel foods and on the role of EFSA on risk assessment, with a focus on the possible role of these foods in the food system and in the diet.